Effects of Intracanal Curcumin and Aloe vera on pH Changes in Simulated Root Surface Resorption Defects: An In vitro Study - Shahmorad Moghanlou, Aysan; Samiei, Mohammad; Shakoui Bonab, Sahar (Iranian Endodontic Journal, 2022)
Introduction: Commonly used medicaments in the treatment of external inflammatory root resorption (EIRR) have shown adverse effects; resulting in an increasing tendency to employ natural and/or herbal medication. The present in vitro study aimed to evaluate the effects of curcumin and aloe vera, as two natural medicaments, on the changes of pH in external root surface defects; and compare their outcomes with the results obtained from the application of calcium hydroxide, as a conventional medicament used in endodontic treatments. Materials and Methods: In the current investigation, 92 permanent teeth, with a single root canal, were randomly divided into four groups. Similar cavities were created on the buccal surfaces of roots, 5 mm from their apices. The root canals in each of the study groups were filled with curcumin, aloe vera, calcium hydroxide or normal saline. The pH was measured after 20 min (i.e. the baseline), 1, 7, 14, 21, and 28 days using a digital pH meter. The data were analysed using repeated-measures ANOVA and the statistical significance was set at P<0.05. Results: At the baseline, day 1 and day 7, the mean pH of both curcumin and aloe vera groups was higher than the mean pH of calcium hydroxide and normal saline groups (P<0.05). On day 14, the mean pH of aloe vera group was higher than that of calcium hydroxide and normal saline groups (P<0.05). On days 21 and 28, the mean pH of aloe vera group was higher than the mean pH of all the other groups (P<0.05). All other intergroup differences were not statistically significant at each time point (P>0.05). Conclusion: The current in vitro study demonstrated that aloe vera was more alkaline than curcumin; nevertheless, both groups exhibited more alkalinity than calcium hydroxide.